Zinc Triflate Catalyzed Tandem One-Pot Regioselective Synthesis of Highly Functionalized Pyrrole Derivatives - Alam, Mohammad Sarwar; Kale, Balkrishna Ramchandra; Hamid, Hinna; Kale, Raju (Synlett, 2025)
An efficient, zinc triflate catalyzed, tandem cyclization for the synthesis of highly functionalized pyrrole derivatives of potential medicinal significance has been developed. The four components—an arylamine, an aldehyde, acetylacetone, and nitromethane—were effectively cyclized in a single step with four different bonds (C–C and C–N). The readily available materials, broad substrate scope, excellent functional-group tolerance, mild conditions, scalability, and excellent yields of high-purity products are attractive features of this newly developed protocol.
Keywords: zinc triflate; one-pot reaction; tandem reaction; cyclization; pyrroles; medicinal chemistry